Corilagin Alleviates Nonalcoholic Fatty Liver Disease in High-Fat Diet-Induced C57BL/6 Mice by Ameliorating Oxidative Stress and Restoring Autophagic Flux - Zhang, Rong; Chu, Kexin; Zhao, Nengjiang; Wu, Jingjing; Ma, Lina; Zhu, Chenfang; Chen, Xia; Wei, Gang; Liao, Mingjuan (Frontiers in Pharmacology, 2020)
Corilagin (Cori) possesses multiple biological activities. To determine whether Cori can exert protective effects against non-alcoholic fatty liver disease (NAFLD) and its potential mechanisms. C57BL/6 mice were fed with high-fat diet (HFD) alone or in combination with Cori (20mg/kg, i.p.) and AML12 cells were exposed to 200 μM PA/OA with or without Cori (10 μM or 20μM). Phenotypes and key indicators relevant to NAFLD were examined both in vivo and in vitro. In this study, Cori significantly ameliorated hepatic steatosis, confirmed by improved serum lipid profiles, and hepatic TC, TG contents, and the gene expression related to lipid metabolism in livers of HFD mice. Moreover, Cori attenuated HFD-mediated autophagy (including mitophagy) blockage by restoring autophagic flux, evidenced by increased number of autophagic double vesicles containing mitochondria, elevated LC3II protein levels, decreased p62 protein levels, as well as enhanced co-localization of autophagy-related protein (LC3, Parkin) and mitochondria. In accordance with this, Cori also reduced the accumulation of ROS and MDA levels, and enhanced the activities of anti-oxidative enzymes including SOD, GSH-Px, CAT. In addition, Cori treatment improved mitochondrial dysfunction, evidenced by increased mitochondrial membrane potential (ΔΨm). In parallel with this, Cori decreased mitochondrial DNA oxidative damage, while increased mitochondrial biogenesis related transcription factors expression, mitochondrial DNA content and oxygen consumption rate (OCR). In conclusion, these results demonstrates that Cori is a potential candidate for the treatment of NAFLD via diminishing oxidative stress, restoring autophagic flux, as well as improving mitochondrial functions.